The impact of political and economic stability on tourist arrivals of sri lanka after liberalisation - Pushparajah, S.; Vijayakumar, S. (Faculty of Management Studies and Commerce, University of Jaffna, Sri Lanka, 2019)
The tourism sector and the tourist arrivals of Sri Lanka have significantly been affected by the economic instability and the political instability. The main objective of the study is to identify and find out the impact and association of political and economic stability on tourist arrivals in Sri Lanka. Therefore the study investigates more specifically on the contribution made by the Sri Lanka tourism on gross domestic product and economic development. The researcher has adopted the time series data from 1980-2017and used Eview for analysis of the relationship between the variables. Then Unit root test, Multiple regression, Johnson test, Heteroscedasticity Test, Breusch-Godfrey Serial Correlation LM Test are used as a tool for data analysis with a help of time series data approach. In this study, military expenditure and gross domestic product which are independent variables have been employed as proxy variables. According to the analysis, military expenditure and gross domestic product have significant impact on tourist arrivals because of the very fact that both military expenditure and gross domestic product’s P value is less than 0.05%.The model revealed that there is negative and significant association between the tourist arrivals and military expenditure. Nevertheless, there is positive and significant association between GDP and the tourist arrivals. According to the Adjusted R- squared value (0.81), 81% of variation in tourist arrivals has been explained by political and economic stability. Further, the results proved that there is a co-integration relationship among variables. Thus, this results revealed that the relationship between tourist arrivals and both GDP and military expenditure are in long term.
Keywords: Economic stability; Political stability; Multicollinearity; Long run association; Tourist arrivals; GDP